THE EFFECT OF NON PERFORMING LOAN, CAPITAL ADEQUACY RATIO AND INCOME SMOOTHING ON LOAN LOSS PROVISION WITH RESTRUCTURING POLICY AS MODERATE VARIABLES - Oryza Sativa Heningtyas; Atik Isniawati; Veronica Tri Astuti (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2021)
This study wants to examine the effect of NPL on LLP, CAR on LLP, EBTP on LLP moderated by restructuring policies before and after the Covid-19 pandemic. Of these three variables have similarities that have a direct or indirect impact on the performance and capacity of bank debtors. This impact has the potential to disrupt banking performance, which turns out to be changing and disrupts financial system stability which has an impact on Indonesia's economic growth due to the Covid-19 pandemic. This study uses secondary data, the sample selection method used in this study is purposive sampling method with a sample of 55 companies and 1100 observation data. This type of research is quantitative research, data analysis using multiple linear regression and group moderation test. These findings indicate that the NPL and income smoothing variable has a significant positive effect on LLP. From the results of the study, it can be concluded that banks in Indonesia increase LLP when the NPL increases as an effort to mitigate the risk of loss.CAR has an insignificant negative effect on LLP which indicates the absence of capital management. The results of the EBTP and LLP tests have a significant positive effect, it can be concluded that there is an indication of income smoothing (IS) activity in conventional banking in Indonesia. Meanwhile, policy restructuring is not able to moderate the relationship between NPL, CAR, Income Smoothing and LLP.Keywords: NPL, CAR, Income Smoothing, LLP, Restructuring Policy